2020
DOI: 10.3390/jcm9082422
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Korean Medicine Treatment on the Incidence of Parkinson’s Disease in Patients with Inflammatory Bowel Disease: A Nationwide Population-Based Cohort Study in South Korea

Abstract: We aimed to investigate the association between Korean medicine (KM) treatment and the risk of Parkinson’s Disease (PD) in patients with inflammatory bowel disease (IBD) in South Korea. This study analyzed data from the National Health Insurance Service-Senior cohort in South Korea. The 1816 IBD patients enrolled in the analysis comprised 411 who received only conventional treatment (monotherapy group) and 1405 who received both conventional and KM treatments (integrative therapy group). The risk of PD in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A retrospective cohort study in South Korea by Noh et al. ( 52 ) compared conventional treatment and combination treatment for IBD and found a reduced risk of PD in the combined treatment group without normal controls, because of which it was excluded. Paakinaho et al.’s study ( 23 ) examined the association between RA and PD by improving anti-rheumatic drugs, which did not match the data of this study; thus, it was excluded from the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective cohort study in South Korea by Noh et al. ( 52 ) compared conventional treatment and combination treatment for IBD and found a reduced risk of PD in the combined treatment group without normal controls, because of which it was excluded. Paakinaho et al.’s study ( 23 ) examined the association between RA and PD by improving anti-rheumatic drugs, which did not match the data of this study; thus, it was excluded from the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the pathogenesis of IBD and PD, there are some similar pro-inflammatory factors in the inflammatory process of both diseases, such as TNF-α and IL-1β. Dopaminergic degeneration of central substantia nigra striatum with intestinal inflammation is related to the increase of TNF-α and IL-1β ( 47 ). Peter et al ( 14 ) reported an interesting American cohort study that the incidence rate of PD in patients with IBD treated with anti-TNF was reduced by 78% compared with those without exposure, which supported the role of systemic inflammation in the pathogenesis of both IBD and PD.…”
Section: Discussionmentioning
confidence: 99%
“…IBD was defined as the presence of a major or minor diagnostic code associated with ICD-10 code K50 for CD or ICD-10 code K51 for UC, with special V codes (V130 for CD and V131 for UC) provided by the Rare Intractable Diseases (RID) programme, which is part of the NHIS [ 18 ]. In Korea, the RID programme provides a copayment reduction of approximately 10% for various rare and intractable diseases including IBD.…”
Section: Methodsmentioning
confidence: 99%